NUMBERS CONVERSION PROGRAM TO BE USING CAPITALS AND PRONUNCIATION MS VISUAL BASIC 6.0 - Hertanto Purwanto; Yuce Yuliani. Skom. MM Yuce Yuliani. Skom. MM (Jurnal Sistem Informasi, 2002)
The program is very important to help companies engaged in telecommunicationsinformation services as a substitute operator, thereby reducing the operational costs ofthe company. In addition the program also can help to achieve work efficiency of theData Entry especially the parts that need spelled out from a figure, and also makes iteasy for consumers to get information quickly and accurately regardless of humanerror that often occurs.